Headache changes in individuals with migraine post-Covid-19: general characteristics of the acute phase and worsening of the migraine pattern - Silva, Aline Vitali da; Peçanha, Marianne Klock; Freitas, Amanda Pasquini de; Bello, Valéria Aparecida; Poli, Regina Célia (Headache Medicine, 2023)
Introduction The aim of this study was to investigate how infection with SARS-CoV-2 affected headache in individuals with migraine, and to identify characteristics associated with a worsening of the migraine post COVID-19. Methods Observational study composed of 157 individuals with migraine and who had been infected with the SARS-CoV-2 virus. They were recruited from the database of the headache research group at the Pontifical Catholic University of Paraná. The participants responded online to questions about their anthropometric data, history of infection with SARS-CoV-2, presence and characteristics of the headache in the acute phase, perception of a worsening of the migraine after infection, use of analgesics and prophylactic migraine medication. Validated digital questionnaires were used: Migraine Disability Assessment (MIDAS), Beck Depression Inventory (BDI) and Allodynia Symptom Checklist (ASC-12). The results of these questionnaires were compared to values previously recorded in the database, this information having been obtained prior to the infection with COVID-19. Conclusion Individuals who notice a worsening in migraine post-COVID-19 have a more severe migraine condition prior to infection, have more prominent headache during the acute phase and, subsequently, present with greater disability.